PENGARUH VARIAN PRODUK DAN KEBIJAKAN HARGA TERHADAP KEPUTUSAN PEMBELIAN BAHAN KEBUTUHAN POKOK DI RETAIL BISNIS RIN MART SIDOARJO - Yuni Kartikasari; Tri Sudarwanto (Jurnal Pendidikan Tata Niaga (JPTN), 2022)
The following research aims to analyze and explain the effect of product variants and pricing policies on purchasing decisions for basic necessities in the retail business of Rin Mart Sidoarjo. This type of research uses quantitative research by determining the sample using the slovin formula. Data collection techniques by distributing questionnaires are given to consumers who have purchased basic necessities at the Rin Mart Sidoarjo retail business. The data analysis technique in this study used multiple linear regression analysis techniques. From the data analysis that has been done, the product variant variable (X1) has a positive influence on purchasing decisions (Y). The price policy variable (X2) has a positive influence on purchasing decisions (Y). Product variance (X1) and price policy (X2) simultaneously influence the purchasing decision (Y) of basic necessities in the retail business of Rin Mart Sidoarjo. Keywords: product variant, price policy, purchase decision.